From the Franco-Russian Alliance (1894) to the Franco-Soviet Treaty on Mutual Assistance (1935): Two Rounds of Acquaintance with the Fine Art of the Ally - Ksenia Andreevna Bespalova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2024)
This article considers the emergence of mutual interest in the art of France and the Russian Empire in the period from the conclusion of the Franco-Russian Alliance in 1894 to the Franco-Soviet Treaty of Mutual Assistance in 1935. The author of the article singles out two stages in the appeal to the fine arts of a friendly state: the turn of the twentieth century and the period following 1924 after the recognition of the USSR by France. Describing the first period of interest in the fine arts, the author refers to events that took place in the Russian Empire and in France, organised with the cooperation of French and Russian cultural and art figures. It is concluded that the organisation of numerous art exhibitions in both countries testified to the mutual desire of the parties to get acquainted with the novelties of the art genre of the other, as well as comprehend the episodes of common history (in particular, the war of 1812). Describing the new round of acquaintance with the culture of France and the USSR after 1924 and drawing on sources from the funds of the Russian State Archive of Literature and Art, the author proves that both in France and in the USSR, interest in the fine arts of each other remained and was fueled by the desire of the People’s Commissariat of Education of the RSFSR to cooperate with France. The work focuses on the fact that it was the smaller exhibitions through which the complementarity and commonality of cultures of both countries were recognised and which were the main place of cultural interaction. The author concludes that despite the different political systems in France and the Russian Empire / USSR, cultural ties between the two countries played a significant role, both at the turn of the century and in the 1920s–1930s, when cultural ties between them became a new impulse due to their respective revolutionary past.